Relational Aggression vs. Well-Being: Uncovering the Impact of Relational Harm Among Adolescents - Normalasari, Cahya; Biju Thomas, Smita; Nazri Abdul Rahman , Mohd; Syahputra, Yuda (JITSS (Journal of Innovation and Trend in Social Sciences), 2025)
The purpose of this study was to investigate relational aggression if any, the detrimental consequences of relational aggression for eighth-grade students’ psychological well-being at one of the junior high schools in Jakarta. The present research utilized a quantitative correlational research design involving 150 students, randomly selected. Data were collected through questionnaires and analyzed using simple regression with IBM SPSS version 20. The research report showed a significance value of .000 (p < .005); with a t value of –10.054 indicating relational aggression had a significant negative impact on the students’ psychological well-being. The negative t-value indicates an inverse correlation between relational aggression the students’ psychological well-being; the higher the relational aggression the less psychological well-being students exhibited on the measure. The R Square value of 0.406 indicates that relational aggression accounted for 40.6% in the variance for psychological well-being. While the remaining variance of 59.4% would be indicating variables not previously assessed in this study. The model provides a suitable account to predict psychological well-being. Relational aggression must be taken into consideration if we expect to promote positive mental health for students.